Study of the Working of the Aided Voluntary Agencies in Social Welfare Programme - Planning Commission (Planning Commission, 1970)
The mode of recruitment of the paid staff for the voluntary organisations was not uniform. Most of the well-established organisations usually recruited staff by advertising the post or with the help of employment exchanges. However, the smaller organisations recruited their staff through personal acquaintance or references. As a result, there was no uniform scale of pay or fixed salaries offered in different voluntary organisations in the country. Most of the voluntary and paid workers in smaller organisations did not have the adequate background and training in social welfare work.
Programme Evaluation Organisation Planning Commission
Programme Evaluation Organisation Planning Commission